Federal Implications of Northern Territory Statehood - Harwood, Jeffrey; Phillimore, John; Fenna, Alan (Blackwell Publishing Asia P/L, 2010)
Just over a decade since the failed referendum of 1998, statehood for the Northern Territory (NT) is back on the political agenda. The achievement of statehood would be a first for Australian federalism, where no new state has been created or admitted since Federation. Following a discussion of the concept of statehood and how it might be achieved, it traces the political development of the NT. The article then examines the implications of NT statehood for the Australian federation and finds that statehood would facilitate constitutional change in the federation by lowering the threshold required for success in a national referendum. Statehood may also raise questions about the equal representation in the Senate of less populous states. However, statehood would have no effect upon financial arrangements with the Commonwealth, the standing of the Northern Territory at COAG meetings, or the legal standing of the other states.